System of rice intensification in rural Bangladesh: adoption, diffusion and impact - Barrett, Chris; Fafchamps, Marcel; Islam, Asad; Malek, Abdul; Pakrashi, Debayan (International Growth Centre, 2022)
The main objective of this study is to understand the network characteristics and incentive mechanism for successful adoption and diffusion of the system of rice intensification(SRI). The researchers examine whether village-level social networks among farmers can be used to promote information, as well as the uptake of SRI. They also analyse whether and how a farmer’s decision to adopt a new technology depends upon the adoption decision of other farmers in his social group. Then they examine the impact of SRI on rice yield and profitability. The latter enables the researchers to examine if the observed productivity gains measured elsewhere using observational studies can be substantiated using a large randomized control trial (RCT). To date, there has not been any experimental study examining the impact, adoption and diffusion mechanism of SRI technology in any setting. So, this study is the first examining the effects, take-up and diffusion of SRI to a wider scale using randomized controlled field experiments.